Genially Developing Digital Media Based on Problem Based Learning to Increase Learning Motivation in Mathematics Lessons - Auliya; Ridania Ekawati; Sekar Harum Pratiwi (PT Suria Academic Press, 2026)
This research is motivated by the use of learning media in grade IV of SDN 32 Bungo Pasang, Padang City, which is still limited to images, so it has not been able to actively engage students. The research aims to develop valid, practical, and effective Genially digital media to meet learning needs and increase student learning motivation. This type of research is Research and Development (R&D) with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Validity tests were carried out by validators using a validity questionnaire, practicality was assessed by teachers, and effectiveness was assessed by 26 students through a motivation questionnaire. The results showed that Genially media obtained a validity score of 92% (very valid), practicality of 97.5% (practical), and effectiveness of 90% (very effective). These findings indicate that Genially digital media meets all assessment criteria and is able to increase student motivation, activeness, and enthusiasm for learning in mathematics learning. This media can also be used by teachers as an alternative interactive learning in elementary schools.